Genetic and Epigenetic Factors at COL2A1 and ABCA4 Influence Clinical Outcome in Congenital Toxoplasmosis - Jamieson, Sarra E. (Public Library of Science, 2008)
BACKGROUND: Primary Toxoplasma gondii infection during pregnancy can be transmitted to the fetus. At birth, infected infants may have intracranial calcification, hydrocephalus, and retinochoroiditis, and new ocular lesions can occur at any age after birth. Not all children who acquire infection in utero develop these clinical signs of disease. Whilst severity of disease is influenced by trimester in which infection is acquired by the mother, other factors including genetic predisposition may contribute. METHODS AND FINDINGS: In 457 mother-child pairs from Europe, and 149 child/parent trios from North America, we show that ocular and brain disease in congenital toxoplasmosis associate with polymorphisms in ABCA4 encoding ATP-binding cassette transporter, subfamily A, member 4. Polymorphisms at COL2A1 encoding type II collagen associate only with ocular disease. Both loci showed unusual inheritance patterns for the disease allele when comparing outcomes in heterozygous affected children with outcomes in affected children of heterozygous mothers. Modeling suggested either an effect of mother's genotype, or parent-of-origin effects. Experimental studies showed that both ABCA4 and COL2A1 show isoform-specific epigenetic modifications consistent with imprinting. CONCLUSIONS: These associations between clinical outcomes of congenital toxoplasmosis and polymorphisms at ABCA4 and COL2A1 provide novel insight into the molecular pathways that can be affected by congenital infection with this parasite.